Pemanfaatan Limbah Lidi Kelapa Sawit Ecofriendly Sebagai Zero Waste Style Untuk Peningkatan Pendapatan Pada Kelompok Ibu Rumah Tangga di Rokan Hulu, Provinsi Riau - Annisa Mardatillah; Sri Rezeki; Rosmayani Rosmayani (PELANTAR PRESS, 2022)
Oil palm plantations store a lot of potential resources that open up business opportunities in the upstream and downstream sectors. Unfortunately, this activity creates a new problem, namely generating waste that has not been utilized optimally. So far, waste from palm oil production has not been utilized optimally, including palm oil stick waste which is only wasted until it rots. Meanwhile, it helps create new business opportunities in the eco-friendly creative economy by utilizing palm oil waste. The partner group in this PKM activity is a group of housewives who are less productive in Kepenuhan District, Rokan Hulu Regency, Riau. The reason why the less productive group of housewives should be employed is because the prices of basic goods do not increase in proportion to household income, which leads to household stability and growth due to uncertainty. This situation encourages women, especially housewives, not only to do housework, but also to involve them in the business world to support the family economy. The activity provides counseling materials related to zero waste style and entrepreneurship as well as training on the utilization of palm oil stick waste into creative products with economic value.